Repression of SRF target genes is critical for Myc‐dependent apoptosis of epithelial cells. (20th April 2015) - Wiese, Katrin E; Haikala, Heidi M; von Eyss, Björn; Wolf, Elmar; Esnault, Cyril; Rosenwald, Andreas; Treisman, Richard; Klefström, Juha; Eilers, Martin
Abstract Oncogenic levels of Myc expression sensitize cells to multiple apoptotic stimuli, and this protects long‐lived organisms from cancer development. How cells discriminate physiological from supraphysiological levels of Myc is largely unknown. Here, we show that induction of apoptosis by Myc in breast epithelial cells requires association of Myc with Miz1. Gene expression and ChIP‐Sequencing experiments show that high levels of Myc invade target sites that lack consensus E‐boxes in a complex with Miz1 and repress transcription. Myc/Miz1‐repressed genes encode proteins involved in cell adhesion and migration and include several integrins. Promoters of repressed genes are enriched for binding sites of the serum‐response factor (SRF). Restoring SRF activity antagonizes Myc repression of SRF target genes, attenuates Myc‐induced apoptosis, and reverts a Myc‐dependent decrease in Akt phosphorylation and activity, a well‐characterized suppressor of Myc‐induced apoptosis. We propose that high levels of Myc engage Miz1 in repressive DNA binding complexes and suppress an SRF‐dependent transcriptional program that supports survival of epithelial cells.